Factors Affecting the Intention of Inpatient Revisit Mediated by Patient Trust - Adjra Safira Hidayat; Sarwo Edy Handoyo (UNIVERSITAS PAKUAN, 2025)
This study aims to examine the influence of health service quality and patient satisfaction on revisit intention, with patient trust as a mediating variable, among hospitalized patients at Ciawi Regional Hospital. A quantitative method with a causal-comparative design was employed, and primary data were collected through questionnaires distributed to 108 inpatients. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS version 4.0. The measurement model evaluation indicated that all indicators fulfilled validity and reliability requirements, including convergent and discriminant validity assessed through Fornell-Larcker criteria, cross-loadings, and HTMT ratio. In the structural model analysis, the model demonstrated strong explanatory power, with an R-square value of 74.4% for revisit intention and 40.7% for patient trust, and showed predictive relevance with a Q-square value of 0.668. Hypothesis testing revealed that both health service quality and patient satisfaction had positive and significant effects on revisit intention and patient trust. Furthermore, patient trust was found to have a positive and significant influence on revisit intention. Mediation analysis confirmed that patient trust significantly mediated the relationship between health service quality and patient satisfaction on revisit intention. These findings support the applicability of the Theory of Planned Behavior in healthcare services and highlight the critical role of patient trust in bridging service quality and satisfaction to promote revisit intention. The study offers practical recommendations for Ciawi Regional Hospital to enhance service quality and build patient trust as strategies to increase patient loyalty and revisit frequency.